Business factors that impact customer value to increase online adoption from free to paid-for content - Hershowitz, Marc (My University, 2016)
The last decade has seen considerable change in the traditional news media space. The advent of the internet has brought the likes of Social media platforms (Facebook, Instagram, and Twitter etc.), Search companies (Google), Digital/online platforms & websites to the fore. These platforms have become ubiquitous to our lives and this proliferation has altered our content & news consumption patterns, types of content we read and are interested in, as well as changes in delivery/distribution mechanisms to users and consumers. Technological change through the channel as well as a dependency of the internet boom, the rise of social platforms, search companies, digital publishing, mobile telephony, smart phones, availability to High speed & cheap broadband as well as unclear IP and Copyright laws across the internet have resulted in a period of unprecedented technological disruption to many previously impervious business models- none more so than traditional news print industry. Chyi (2012) states that the intensity of the debate around the subject of ‘paywalls’ as it pertains to the value of news and the future of journalism is significant; however studies have not succeeded at conceptualising the issue correctly. Part of the basis of this lack of research is a function of ‘paywalls’ being relatively new and as such there is a lack of historical and comparative data. Chyi, found that the public at large had small interest in paying for online news and thus “news publishers may find it difficult to rely on the subscription model to achieve economic viability “(Chyi 2005, 141). She further suggested that the primary reason for users’ unwillingness to pay for online news was due to the perceived lack of “unique value” and ultimately considered an inferior good. This argument is countered by Van der Wurff (2012, 245), who purported that “good journalism adds value to news because of the positive outcomes to keep citizens informed”. According to Myllyahthi, (2014) there has been a vast uptake since 2012 in these same newspaper organisations introducing numerous new business models geared around online subscriptions- commonly known as ‘paywalls’. This has been brought about as a means to attempt to offset and compensate for the losses in the traditional print advertising market as well as declines in hardcopy subscriptions. This however, has proved to be a significant challenge as stated by Rosentsiel, Jurkowitz and Ji(2012), the increases made on digital platforms has not made up for commensurate losses on print. This can be attributable to two key reasons: the value of each additional (1) digital dollar is worth seven (7) print advertising dollars. The 2nd significant reason is the fact that these same publishers took the strategic decisions many years ago to offer online news content for free in order to chase traffic/audience size (in industry terms scale) on their digital platforms with the hope that once the that scale had been reached they would be positioned appropriately to exploit their respective vast market shares. What they perhaps could not have anticipated is the way in which the likes of Google, Facebook, AOL, and Yahoo etc. would not only permeate and challenge their existing business and in particular pricing models but also be able to reach and attract audiences far exceeding the traditional news industry captive audience. Dutta, (2012), suggests that ultimately online readers have a “real consumption choice, because of the monetary sacrifice involved.” Brandsetter and Schmalhofer reason that “readers are only willing to pay for online content if it is offering added value and is not freely available elsewhere (Journalism Practice, 2014), users are willing to pay for content if it holds value( Wang et al. 2005), and Hermansson ,2013), added value by providing unique information (Brandsetter, Schmaloffer, 2014). The purpose of this study was to evaluate and determine the value drivers of moving from free to fee for online content. The research was conducted using quantitative data collection methods.
Keywords: Digital media; Internet--Economic aspects; Online journalism